2014
DOI: 10.1101/lm.032177.113
|View full text |Cite
|
Sign up to set email alerts
|

The role of rewarding and novel events in facilitating memory persistence in a separate spatial memory task

Abstract: Many insignificant events in our daily life are forgotten quickly but can be remembered for longer when other memorymodulating events occur before or after them. This phenomenon has been investigated in animal models in a protocol in which weak memories persist longer if exploration in a novel context is introduced around the time of memory encoding. This study aims to understand whether other types of rewarding or novel tasks, such as rewarded learning in a T-maze and novel object recognition, can also be eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 45 publications
(74 reference statements)
3
45
0
Order By: Relevance
“…In the future, projects investigating whether and how novelty exploration, emotional arousal or extrinsic reward may boost long-term memory formation, especially for material that does not inspire curiosity or intrinsic motivation, could help translate the present body of neuroscientific knowledge to practical applications. A first animal demonstration showed that novelty exploration indeed can facilitate consolidation in subsequent declarative memory formation and lead to improved recall 24 h later (Salvetti et al, 2014). Similar effects of novelty exploration in humans, have so far been reported for immediate memory tests (Fenker et al, 2008;Schomaker et al, 2014).…”
Section: Resultsmentioning
confidence: 55%
“…In the future, projects investigating whether and how novelty exploration, emotional arousal or extrinsic reward may boost long-term memory formation, especially for material that does not inspire curiosity or intrinsic motivation, could help translate the present body of neuroscientific knowledge to practical applications. A first animal demonstration showed that novelty exploration indeed can facilitate consolidation in subsequent declarative memory formation and lead to improved recall 24 h later (Salvetti et al, 2014). Similar effects of novelty exploration in humans, have so far been reported for immediate memory tests (Fenker et al, 2008;Schomaker et al, 2014).…”
Section: Resultsmentioning
confidence: 55%
“…Novelty enhances the phosphorylation state of CREB in the hippocampus (43) and activates hippocampal MAPKs (44). Salvetti et al (45) showed that novelty presented after weak memory training can promote the memory consolidation of a spatial task.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are findings suggesting the existence of a similar process operating in LTM formation in humans (Ballarini et al, 2013;Dunsmoor, Murty, Davachi, & Phelps, 2015). Besides OF, other experiences such as objects' exploration in a novel arena, a novel taste, a Morris water maze session, a contextual fear conditioning reminder session, contextual fear conditioning extinction session or a rewarded T-maze task were further described as protein supplier events that promote unrelated memories (Ballarini et al, 2009;Cassini et al, 2013;Dong et al, 2012;Salvetti, Morris, & Wang, 2014). Considering the plethora of data about the modulatory effect on memory processes caused by stress or by the administration of glucocorticoids (Cadle & Zoladz, 2015;Joëls et al, 2006;Sandi & Pinelo-Nava, 2007) we considered that a stressful event could influence unrelated memory formation by providing or competing for protein resources.…”
Section: Introductionmentioning
confidence: 99%